Synthesis of ecofriendly fluorescent carbon dots and their biomedical and environmental applications - Joshi, Preeti Nigam; Mathias, Anjelica; Mishra, Abhishek (Materials Technology, 2018)
Green Synthesis of nanoparticles is an emerging field with enormous advantages over conventional synthesis methods. Herein we have reported a green method for the preparation of water soluble polydisperse carbon dots (c-dots) from Cocos nucifera frond pinnae by a modified version of the `single step hydrothermal carbonization'. C-dots having blue emission were obtained with this method and we further evaluated the effect of metal ions interactions on c-dots, as a sharp decrease in photoluminescence was observed. The synthesized c-dots were found bioactive against B.subtilis, M. smegmatis and S. aureus as determined by the well diffusion assay. We also explored nanotheranostic applications of c-dots as biosensor matrix in DNA hybridization sensor for pancreatic cancer and in bioimaging of cancer cells. This study demonstrated that c-dots can be explored for numerous biomedical and environmental applications in a variety of fields owing to the cost effective synthesis, biocompatibility and excellent physico-chemical properties.
Keywords: Carbon dots; differential pulse voltammetry; DNA hybridization sensor; green synthesis; Pancreatic Cancer